Ethics of ECPR research. (December 2021) - Suverein, Martje M.; Shaw, David; Lorusso, Roberto; Delnoij, Thijs S.R.; Essers, Brigitte; Weerwind, Patrick W.; Townend, David; van de Poll, Marcel C.G.; Maessen, Jos G.
Abstract: The design of emergency medicine trials can raise several ethical concerns – risks may be greater, and randomisation may have to occur before consent. Research in emergency medicine is thus an illuminating context to explore the interplay between risk and randomisation, and the consequences for consent. Using a currently running trial, we describe possible concerns, considerations, and solutions to reconcile the conflicting interests of scientific inquiry, ethical principles, and clinical reality in emergency medicine research.